Attitudes and perspectives of healthcare workers on treating chronic hepatitis C infection in children and adolescents - Malik, Farihah; Easterbrook, Philippa; Indolfi, Giuseppe; Thorne, Claire (Frontiers in Public Health, 2025)
Background and aimsThere are gaps in knowledge about the values and preferences of healthcare workers (HCW) with respect to treatment of children and adolescents living with chronic hepatitis C (HCV) infection. This study was carried out to identify these values and preferences as part of the evidence required to update World Health Organization (WHO) hepatitis C guidelines.MethodsAn online survey was designed and conducted during August/September 2021. Survey questions were developed to address two key questions about treatment of children and adolescents: who to treat, and which direct acting antiviral (DAA) regimens to use. The survey was circulated by the WHO to nine networks providing care to children and adolescents living with HCV infection, with respondents requested to cascade further within their networks.ResultsA total of 137 individuals from 38 countries responded to the survey. There was a trend toward higher preference for treating children of older age groups; 60% of respondents reported a strong preference for treating (i.e., stating they were very likely or likely to treat) children aged 3 to <6 years, 81 and 95% indicated strong preferences for treating those aged 6 to <12 years and 12 to <18 years, respectively. The most preferred DAA regimens for treatment across all age groups were: sofosbuvir/velpatasvir (SOF/VEL), sofosbuvir/ledipasvir (SOF/LDV), and glecaprevir/pibrentasvir (GLE/PIB). These were also reported to be the most commonly available drug regimens at respondents’ facilities.ConclusionThis survey provides insights from a heterogenous sample of HCWs from across the world with respect to their expressed priorities and preferences for the treatment of children and adolescents with chronic HCV.